Prenatal Diagnosis - Hahn, Sinuhe; Jackson, Laird G.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2008)
With molecular biology now allowing greater accuracy in prenatal diagnosis given amounts of fetal material as small as single cells, a major current focus has grown in the development of rapid, cost-effective diagnoses. In Prenatal Diagnosis, top experts provide cutting edge applications for the rapid assessment of fetal aneuploidies and Mendelian disorders on fetal material gained by invasive approaches, as well as procedures being validated for routine, non-invasive clinical analysis of cell free fetal DNA. Following the Methods in Molecular Biology$1!" (Bseries format, the chapters feature step-by-step laboratory protocols, lists of the necessary materials, and tips on troubleshooting and avoiding known pitfalls. Thorough and state-of-the-art, Prenatal Diagnosis is an ideal volume for researchers and molecular biologists invested in ever-growing field of prenatal medicine.s
Invasive Approaches -- Spectral Karyotyping (SKY): Applications in Prenatal Diagnostics -- Characterization of Prenatally Assessed De Novo Small Supernumerary Marker Chromosomes by Molecular Cytogenetics -- Rapid Prenatal Aneuploidy Screening by Fluorescence In Situ Hybridization (FISH) -- Application of Multi-PRINS to Simultaneously Identify Chromosomes 18, X, and Y in Prenatal Diagnosis -- Prenatal Diagnosis Using Array CGH -- Prenatal Detection of Chromosome Aneuploidy by Quantitative Fluorescence PCR -- Real-Time Quantitative PCR for the Detection of Fetal Aneuploidies -- MLPA for Prenatal Diagnosis of Commonly Occurring Aneuploidies -- MALDI-TOF Mass Spectrometry for Trisomy Detection -- Rapid Detection of Fetal Mendelian Disorders: Thalassemia and Sickle Cell Syndromes -- Rapid Detection of Fetal Mendalian Disorders: Tay-Sachs Disease -- Arrayed Primer Extension Reaction for Genotyping on Oligonucleotide Microarray -- A Fast Microelectronic Array for Screening and Prenatal Diagnosis of ?-Thalassemia -- Noninvasive Approaches -- RHD Genotyping from Maternal Plasma: Guidelines and Technical Challenges -- Isolation of Cell-Free DNA from Maternal Plasma Using Manual and Automated Systems -- Fetal DNA: Strategies for Optimal Recovery -- Quantification of Circulatory Fetal DNA in the Plasma of Pregnant Women -- Detection and Quantification of Fetal DNA in Maternal Plasma by Using LightCycler Technology -- Size Fractionation of Cell-Free DNA in Maternal Plasma and Its Application in Noninvasive Detection of Fetal Single Gene Point Mutations -- MALDI-TOF Mass Spectrometry for Analyzing Cell-Free Fetal DNA in Maternal Plasma -- Isolation of Cell-Free RNA from Maternal Plasma -- A Microarray Approach for Systematic Identification of Placental-Derived RNA Markers in Maternal Plasma -- A Novel Method to Identify Syncytiotrophoblast-Derived RNA Products Representative of Trisomy 21 Placental RNA in Maternal Plasma -- Method for Extraction of High-Quantity and -Quality Cell-Free DNA from Amniotic Fluid -- Detection of New Screening Markers for Fetal Aneuploidies in Maternal Plasma: A Proteomic Approach.
Keywords: Medicine; Human genetics; Molecular biology; Obstetrics; Pediatrics; Cell biology; Medicine & Public Health; Pediatrics; Obstetrics/Perinatology.; Human Genetics; Cell Biology; Molecular Medicine; Electronic books